Proceedings of the 2020 ACM SIGSAC Conference on Computer and Communications Security 2020
DOI: 10.1145/3372297.3417254
|View full text |Cite
|
Sign up to set email alerts
|

When the Differences in Frequency Domain are Compensated: Understanding and Defeating Modulated Replay Attacks on Automatic Speech Recognition

Abstract: Automatic speech recognition (ASR) systems have been widely deployed in modern smart devices to provide convenient and diverse voice-controlled services. Since ASR systems are vulnerable to audio replay attacks that can spoof and mislead ASR systems, a number of defense systems have been proposed to identify replayed audio signals based on the speakers' unique acoustic features in the frequency domain. In this paper, we uncover a new type of replay attack called modulated replay attack, which can bypass the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Meanwhile, recent studies have shown ASR systems are vulnerable to various malicious voice attacks [29], [67], [50], [38], [69], [57], [81], [61], [56], [1], [15], [58], [26], [16], [80], [27]. As an alternative representation of voice signals, frequency spectrum has been manipulated by attackers to achieve different attacking goals.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, recent studies have shown ASR systems are vulnerable to various malicious voice attacks [29], [67], [50], [38], [69], [57], [81], [61], [56], [1], [15], [58], [26], [16], [80], [27]. As an alternative representation of voice signals, frequency spectrum has been manipulated by attackers to achieve different attacking goals.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2010s, traditional biometric authentication thrived, for example, using face recognition to unlock a smartphone and fingerprint recognition to unlock a door. Nevertheless, these traditional biometric authentication are vulnerable to replay and presentation attacks [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Two main security attacks have recently emerged to tamper with speaker verification systems. One is called replay attacks that record the legitimate user's speech and then replay it to fool a speaker verification system [19]. Such a sniffing and spoofing attack requires an attacker to obtain a legitimate user's audio.…”
Section: Introductionmentioning
confidence: 99%